Population variability of Ferula foetida genomic DNA, growing in arid Mangistau environment (Experimental biology, 2016)
Interspecific closely-related and population variability of genomic DNA of Ferula foetida (Bunge) Regel has been studied in the comparative plan. The plants grow in Mangistau desert with various levels of edaphic environmental factors.Fresh plants leaves are used for genomic DNA research. DNA was extracted using modified Holmes – Bonner method. 5 out of 30 RAPD primers were selected for PCR with plants genomic DNA. 72 polymorphic and 4 constitutive RAPD-marker bands were obtained for all samples. The phylogenic dendrogram was plotted based on cluster analysis and Popgen 32 software. Dendrogram indicated distinctions or similarity degree between RAPD ranges of the researched objects.As a result of conducted researches the high interspecific and population variability of Ferula was found. It was based on genetic features and growing conditions of species. The results received could make a contribution to the solution of controversial issues in terms of intrageneric systematization. DNA composition data of Ferula foetida which are growing in various regions could make possible the genetic typing medicinal raw products and spices came out from Ferula foetida in various regions for further practice.
Keywords: Ferula foetida; DNA; RAPD; population variability; arid; Mangistau.